2006
DOI: 10.1111/j.1756-2171.2006.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the distribution of firm growth rates

Abstract: Empirical analyses on aggregated datasets have revealed a common exponential behavior in the shape of the probability density of corporate growth rates. We present clear-cut evidence on this topic using disaggregated data. We explain the observed regularities proposing a model in which firms' ability to take up new business opportunities increases with the number of opportunities already exploited. A theoretical result is presented for the limiting case in which the number of firms and opportunities go to infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
209
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(230 citation statements)
references
References 26 publications
19
209
1
1
Order By: Relevance
“…Bottazzi and Secchi [7] replicate these findings and report a Laplace growth distribution for Italian manufacturing firms during the period 1989-96.…”
Section: Firm Growth Distributionssupporting
confidence: 66%
“…Bottazzi and Secchi [7] replicate these findings and report a Laplace growth distribution for Italian manufacturing firms during the period 1989-96.…”
Section: Firm Growth Distributionssupporting
confidence: 66%
“…One of the major robust stylised fact emerging from industrial economics is that the firm growth rates distribution is characterised by wide heterogeneity and a tent shape, whatever the level of sectoral aggregation considered (Stanley et al, 1996;Bottazzi and Secchi, 2006;Coad, 2009;Dosi, 2007). In this respect, due to its inherent nature, the processes leading from innovative input to innovative output may show different effects according to the different positioning of a firm in the growth rates distribution, beyond the effect on growth of the "average firm".…”
Section: Asymmetric Effects Of Innovation Across Growth Quantilesmentioning
confidence: 99%
“…In the probability density function, this would show up as a sharp peak around the modal value, and fat tails. These are features of the exponential power distribution fitted by Bottazzi and Secchi (2006) on growth rates of business firms. As the authors have shown, reinforcing dynamics is a key to the emergence of exponential tails.…”
Section: Variance-size Scalingmentioning
confidence: 99%